Time‐Series Variation in Dividend Pricing - EADES, KENNETH M.; HESS, PATRICK J.; KIM, E. HAN (Journal of Finance, 1994)
ABSTRACT Ex‐dividend day returns vary over time. The ex‐day returns of high‐yield stocks are persistently positive for some time periods and negative for others; in contrast, ex‐day returns of low‐yield stocks are always positive and less variable. We are unable to explain the variation with changes in the tax code, but we do find a strong effect for the introduction of negotiated commissions. We find evidence that corporate dividend capturing is affecting ex‐day returns and confirm the findings of Gordon and Bradford (1980) that the price of dividends is countercyclical.